TECHNOLOGY FOR USING A WORKBOOK TO INCREASE THE EFFECTIVENESS OF PRACTICAL BIOLOGY CLASSES IN GENERAL EDUCATION SCHOOLS - Eshmuratov, Raxat Artikbaevich; Tajimuratova, Shakhnoza Azatovna (SCIENCE and SOCIETY, 2026)
The article highlights the pedagogical and technological aspects of using a workbook to increase the effectiveness of practical biology classes in general education schools. The article analyzes the role of the workbook in practical training, its structure, didactic capabilities, design and application technology, as well as its integration with digital technologies. Based on international and domestic research, it has been scientifically substantiated that the use of assignment notebooks has a positive impact on students' cognitive, affective, and psychomotor competencies. The article is of practical importance for biology teachers, methodologists, and educational technologists.
Keywords: assignment notebook; workbook; practical exercises; biology education; effectiveness; independent study; competency-based approach; digital technologies.